2016
DOI: 10.1039/c6cc00780e
|View full text |Cite
|
Sign up to set email alerts
|

Interface coassembly of mesoporous MoS2based-frameworks for enhanced near-infrared light driven photocatalysis

Abstract: The three-dimensional porous Fe3O4@Cu2-xS-MoS2 framework is reported for the first time. The as-prepared 3D framework exhibits good structural stability, high surface area, enhanced adsorption capacity to substrates, and strong absorption in the NIR range. As a result, such hybrid frameworks exhibit excellent NIR-light photocatalytic activity and stable cycling for the direct arylation of heteroaromatics at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Recently, photo-thermal synergistic catalysis combining thermochemical and photochemical conversion appeared as a promising method for improving the efficiency. [9,10] Sunlight can be divided into three parts: ultraviolet (UV) light (λ < 400 nm), visible (Vis) light (400 nm < λ < 800 nm) and infrared (IR) light (λ > 800 nm). UV-Vis and IR light can induce photocatalytic and thermocatalytic reactions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, photo-thermal synergistic catalysis combining thermochemical and photochemical conversion appeared as a promising method for improving the efficiency. [9,10] Sunlight can be divided into three parts: ultraviolet (UV) light (λ < 400 nm), visible (Vis) light (400 nm < λ < 800 nm) and infrared (IR) light (λ > 800 nm). UV-Vis and IR light can induce photocatalytic and thermocatalytic reactions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Purified by flash chromatography (pentane) to afford a white solid which contains a small amount of 4,4'-dichloro-1,1'-biphenyl. 4-Chloro-1,1'-biphenyl: [18] 4-Chloro-4'-methoxy-1,1'-biphenyl: [18] 2-(4-Fluorophenyl)thiophene: [15] Table 2 3-(4-Fluorophenyl)pyridine: [17] 2-(4-Fluorophenyl)furan: [19] Table 2 2-Methoxy-1,1'-biphenyl: [16] 3-Chloro-1,1'-biphenyl: [20] 3-Methoxy-1,1'-biphenyl: [16] Table 2 …”
Section: General Procedures For Aerobic Heterocoupling Of Two Grignardmentioning
confidence: 99%
“…Figure S7 in the Supporting Information) showed that the obtained PCFs exhibit superparamagneticb ehavior.T he decrease in saturation magnetization compared to Cu 2Àx S@Fe 3 O 4 and Fe 3 O 4 NPs alone is attributed to the nonmagnetic portion. [24] Moreover,t he pore size distribution curve calculated from the adsorptionbranch of the isotherms (insets in Figure3cand d) ex-hibitedt wo maxima at about 11.5 and 28.5 nm for Fe 3 O 4 @Cu 2Àx S-Fs and one maximum at about 15.7 for Fe 3 O 4 -Fs. All the materials showed type IV isotherms,w hichr evealed the presence of mesoporous structures in these frameworks.…”
Section: Results and Discussion Preparation And Characterization Of Pcfsmentioning
confidence: 89%
“…All the materials showed type IV isotherms,w hichr evealed the presence of mesoporous structures in these frameworks. [24] Moreover,t he pore size distribution curve calculated from the adsorptionbranch of the isotherms (insets in Figure3cand d) ex-hibitedt wo maxima at about 11.5 and 28.5 nm for Fe 3 O 4 @Cu 2Àx S-Fs and one maximum at about 15.7 for Fe 3 O 4 -Fs. The specific surfacea rea and total pore volume based on BET analysisw ere calculated to be 33 m 2 g À1 and 0.126 cm 3 g À1 for Fe 3 O 4 @Cu 2Àx S-Fs and 54 m 2 g À1 and 0.195 cm 3 g À1 for the Fe 3 O 4 -Fs, respectively.C ompared with the Fe 3 O 4 @Cu 2Àx SN Ps (3.8 m 2 g À1 ,F igure S8 in the Supporting Information), the high specific surfacea rea of Fe 3 O 4 @Cu 2Àx S-Fs indicates successful preparation of the porous structure.…”
Section: Preparation and Characterization Of Pcfsmentioning
confidence: 89%